2022
DOI: 10.3390/agronomy12010199
|View full text |Cite
|
Sign up to set email alerts
|

Early Effects of Fertilizer and Herbicide Reduction on Root-Associated Biota in Oil Palm Plantations

Abstract: To secure high yield, tropical oil palm plantations are fertilized, and understory vegetation is controlled by chemical clearing with herbicides. These treatments cause a drastic turnover of soil microbes and cause loss of beneficial mycorrhizal fungi. Here, we tested if reduced fertilization and weeding instead of conventional treatments restored beneficial ecological groups associated with roots. We conducted our study one year after the start of the reduced management in large-scale oil palm plantations. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…In agreement with those results, we found that soil pH and soil carbon separated the AMF community structures in plantation and rain forest roots and that soil fertility (phosphorus and C/N ratio) explained the differences between the two rain forest reservations. These results concur with experimental fertilization that led to decreased arbuscular mycorrhizal fungi in tropical forests ( Sheldrake et al., 2017 ) and increased AMF abundances in oil palm plantations upon reduced fertilization ( Ryadin et al., 2022 ). Thus, fertilization and pesticide treatments were likely factors contributing to AMF species reductions in the plantation trees, resulting in lower AMF richness per genus in oil palm and rubber trees than in forest tree genera.…”
Section: Discussionsupporting
confidence: 84%
“…In agreement with those results, we found that soil pH and soil carbon separated the AMF community structures in plantation and rain forest roots and that soil fertility (phosphorus and C/N ratio) explained the differences between the two rain forest reservations. These results concur with experimental fertilization that led to decreased arbuscular mycorrhizal fungi in tropical forests ( Sheldrake et al., 2017 ) and increased AMF abundances in oil palm plantations upon reduced fertilization ( Ryadin et al., 2022 ). Thus, fertilization and pesticide treatments were likely factors contributing to AMF species reductions in the plantation trees, resulting in lower AMF richness per genus in oil palm and rubber trees than in forest tree genera.…”
Section: Discussionsupporting
confidence: 84%
“…Overall, the results of our four-year management experiment provided early indications that mechanical weeding, together with reduced, compensatory fertilization rates in mature, industrial oil palm plantations, can help in minimizing soil nutrient leaching, decrease water pollution risk, eliminate the effect of herbicide on native vegetation and other non-target soil trophic groups 33 , reduce risks to health of plantation workers and thus contribute to sustainability guidelines of certification bodies such as Roundtable of Sustainable Oil Palm 51 . We acknowledge that when analysing across multiple ecosystem functions, the positive effects of the reduced management on multifunctionality may be still small during the first four years of this experiment as there was no significant effect when analysing for individual ecosystem functions.…”
Section: Management Effect On Yield and Profitmentioning
confidence: 73%
“…Additionally, some of the ecosystem indicators were measured as early as one year after the start of the management experiment (Supplementary Table 1). Indeed, studies that investigated the effects of reduced fertilization and mechanical weeding on root-associated soil biota one year after the start of the experiment found no significant treatment effects, which they attributed to legacy effect of conventional fertilization and herbicide use 33 . Similarly, different weeding treatments did not affect vegetation cover (our indicator for erosion prevention), litter decomposition rates (one of our indicators for organic matter decomposition) and soil physical and biochemical characteristics during the first one to two years after treatment 15,26 .…”
Section: Improved Multifunctionality and Biodiversitymentioning
confidence: 99%
“…Changes in soil properties, floristic composition, and structure due to land-use shifts have impacted fine-root mass growth and distribution patterns at fine ecosystem scales [ 23 , 24 ]. In modified landscapes (e.g., artificial grasslands and perennial agroecosystems), changes are intensified by management interventions in the form of soil amendment, tillage, and weed and pest control [ 25 , 26 , 27 ]. Previous studies seeking to understand fine-root mass at different pre- and post-conversion states independently reported a 230–800 g m −2 range for broadleaf and coniferous forests [ 11 , 28 ], 510–950 g m −2 for grass formations [ 11 , 29 ], and 192–637 g m −2 for agroecosystems [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%